Rhinoplasty Training: An Innovative Learning Approach Using Chicken Breast - Freire, Leila; Dolci, José Eduardo Lutaif (Facial Plastic Surgery, 2024)
Mastering rhinoplasty surgical techniques requires extensive learning involving theoretical studies, internships, cadaver laboratories, simulators, nonhuman models, and hands-on practice. A novel method using chicken breast simplifies skill development, offering flexibility and accessibility. Training on chicken breast allows surgeons to refine skills through various techniques and grafts. This study focuses on preservation techniques using chicken as a model. Surgical sequences simulate nasal structures using prepared chicken breasts. Documentation through media illustrates procedures from basic to advanced, using materials akin to traditional rhinoplasty but in reduced quantities. Chicken breast tissue, especially sternal cartilage, offers a suitable substrate for practicing techniques and grafting without live human or cadaveric tissue. This method provides an efficient, safe, and cost-effective approach to learning rhinoplasty.
Keywords: simulated surgical training; rhinoplasty; septoplasty; graft; chicken; sternal cartilage